A cellulose nanocrystal reinforced composite material and its preparation method and application
By using microfluidic control devices to form composite fibers during the mixed process of cellulose nano crystal and polymer resin, and traction and extrusion in the micro -flow tract through a mixed colloid, forming a two -way fiber nanocrystal enhanced composite material to solve the solution The problem of mechanical performance improvement and environmental burden in existing technology has achieved high -performance and environmental composite materials preparation.
Patent Information
- Application Number
- CN202411259884.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The nanocellulose-reinforced polymer-based composite materials prepared in the prior art still have room for improvement in mechanical properties, and the fiber reinforced materials are difficult to recycle, causing environmental burden.
Use a microfluidic device to mix the cellulose nanocrystalline and polymer resin and squeeze out to form a composite fiber, and to traction and extrude in the microflower through the mixed colloid to form the fiber that covers mixed colloids to form a dual -directional structure with a dual -directional structure Cellulose nanocrystal enhanced composite materials.
The mechanical properties of the polymer resin matrix are significantly improved, the adhesion strength between composite fibers is enhanced, and the cellulose nano crystal with excellent mechanical properties enhances the composite material.
Smart Images

Figure CN118791862B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a cellulose nanocrystal reinforced composite material and a preparation method and application thereof. Background Art
[0002] Fiber-reinforced polymer-based composite materials are widely used in aerospace, transportation and other fields due to their advantages of light weight and high strength, in order to save materials and reduce weight. Automobiles made of fiber-reinforced polymer-based composite materials have much lower fuel consumption than steel vehicles due to their greatly reduced weight. At the same time, the mechanical strength of high-performance fiber-reinforced resin-based composite materials such as glass fiber and carbon fiber is far greater than that of ordinary carbon steel, and have extremely high specific strength. However, although the fiber-reinforced composite materials currently used have incomparable advantages, the reinforcement materials made of such fibers are difficult to recycle, which has caused a great burden on the environment.
[0003] Nanocellulose is a green, environmentally friendly, renewable, and new functional polymer nanomaterial. Due to its advantages such as low density, large specific surface area, and high rigidity, it has received extensive attention in the field of resin material reinforcement in recent years. Many methods have been used to prepare nanocellulose reinforced polymer composites. ALEMDAR et al. (ALEMDAR A, SAIN M. Biocomposites from wheat straw nanofibers: morphology, thermal and mechanical properties [J]. Composites Science & Technology, 2008, 68 (2): 557-565.) prepared nanocellulose-starch composites by blending solution casting, which increased the tensile strength and elastic modulus of the nanocomposite by 77% and 145% respectively compared with pure starch. PRAKOBNA et al. (PRAKOBNA K, GALLANDS, BERGLUND L A. High-performance and moisture-stable cellulose-starch nanocomposites based on bioinspired core-shell nanofibers [J]. Biomacromolecules, 2015, 16 (3): 904-912.) prepared nanocellulose-starch composites using the "core-shell" structure method. They dispersed nanocellulose in a branched starch solution, wrapped starch on the cellulose surface to form a core-shell structure, and prepared nanocellulose-starch composites by centrifugal collection and drying to form a film. Compared with the irregular random distribution in the blend solution casting method, nanocellulose is more evenly distributed in the composite material prepared by the "core-shell" structure method, thus further improving the mechanical properties of the matrix.
[0004] Although the nanocellulose-reinforced polymer-based composites prepared in the prior art have achieved significant improvements in mechanical properties such as tensile strength and elastic modulus, nanocellulose is usually irregularly randomly distributed in the composite materials, or is only uniformly dispersed, and there is still much room for improvement in its mechanical properties.
[0005] Therefore, there is an urgent need to develop a green, environmentally friendly, and mechanically sound cellulose nanocrystal-reinforced composite material. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a cellulose nanocrystal reinforced composite material and a preparation method and application thereof. The cellulose nanocrystal reinforced composite material has a dual-oriented structure and excellent mechanical properties.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a cellulose nanocrystal reinforced composite material, the preparation method comprising the following steps:
[0009] (1) mixing cellulose nanocrystals and a polymer resin, and extruding the mixture through a microfluidic device to obtain composite fibers, wherein the mass percentage of the cellulose nanocrystals in the composite fibers is 2.5% to 10.0% (e.g., 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0% or 9.0%, etc.);
[0010] (2) mixing cellulose nanocrystals and an adhesive to obtain a mixed colloid;
[0011] (3) The composite fiber obtained in step (1) is passed through a microfluidic device containing the mixed colloid obtained in step (2) in a microchannel, to be pulled and extruded to obtain fibers with the mixed colloid coated on the surface, and solidified to obtain the cellulose nanocrystal reinforced composite material.
[0012] In the present invention, in step (1), cellulose nanocrystals and polymer resin are heated and mixed, and the polymer resin is melted to obtain a mixed fluid, which is extruded through a microfluidic device to obtain composite fibers. The cellulose nanocrystals in the composite fibers are oriented along the extrusion direction under the action of the microfluidic device, which greatly improves the mechanical properties of the polymer resin matrix; in step (2), the cellulose nanocrystals and adhesive are mixed to form a mixed colloid; in step (3), the composite fibers are extruded through a microfluidic device, and the microchannel of the microfluidic device contains the mixed colloid obtained in step (2), thereby forming fibers with the surface coated with the mixed colloid, which can be bundled, stacked, contacted and merged to form sheets or fiber products of different sizes. When the cellulose nanocrystals in the mixed colloid are extruded through the microfluidic device, they are oriented along the direction of the composite fibers, which enhances the bonding strength between the composite fibers and plays an effective connecting role between the composite fibers. In the cellulose nanocrystal-reinforced composite material, the cellulose nanocrystals in the composite fibers and the mixed colloid are oriented along the same direction, respectively, to form a dual-oriented structure, and the two have a synergistic effect. The obtained cellulose nanocrystal-reinforced composite material has excellent mechanical properties.
[0013] In the present invention, when the mass percentage of cellulose nanocrystals in the composite fiber in step (1) is within a certain range, the higher the content of cellulose nanocrystals, the higher the mechanical strength of the cellulose nanocrystal-reinforced composite material. However, if the mass percentage of cellulose nanocrystals is too high, the proportion of hydrogen bonding of cellulose nanocrystals themselves increases, and agglomeration is likely to occur, which cannot effectively enhance the strength of the composite fiber. The mass percentage of cellulose nanocrystals in the composite fiber in step (1) is 2.5% to 10.0%.
[0014] Preferably, the polymer resin includes any one of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyamide, polycarbonate or acrylonitrile-butadiene-styrene copolymer, or a combination of at least two thereof.
[0015] Preferably, the diameter of the composite fiber is 10.0-200.0 μm, for example, 20.0 μm, 40.0 μm, 60.0 μm, 80.0 μm, 100.0 μm, 120.0 μm, 140.0 μm, 160.0 μm or 180.0 μm.
[0016] Preferably, the mass percentage of cellulose nanocrystals in the mixed colloid in step (2) is 5.0% to 30.0%, for example, 8.0%, 11.0%, 14.0%, 17.0%, 20.0%, 23.0%, 26.0% or 29.0%, and more preferably 15.0% to 25.0%.
[0017] In the present invention, when the mass percentage of cellulose nanocrystals in the mixed colloid is within a certain range, the higher the mass percentage of cellulose nanocrystals, the higher the bonding strength of the mixed colloid. However, if the amount of cellulose nanocrystals added is too high, the cellulose nanocrystals themselves are prone to agglomeration, and the adhesive is difficult to wet and coat the cellulose nanocrystals. The compatibility of the two deteriorates, resulting in a decrease in the mechanical properties of the cellulose nanocrystal-reinforced composite material after curing. To ensure the bonding quality, the mass percentage of cellulose nanocrystals in the mixed colloid is preferably 5.0%-30.0%.
[0018] Preferably, the adhesive includes any one of epoxy resin adhesive, acrylate adhesive, polyurethane adhesive or silicone adhesive, or a combination of at least two of them.
[0019] Preferably, the polyurethane adhesive comprises two-component polyurethane and / or one-component polyurethane.
[0020] Preferably, the polyurethane adhesive comprises water-based polyurethane.
[0021] Preferably, the polyurethane adhesive comprises UV-curable polyurethane.
[0022] Preferably, the mass percentage of composite fibers in the cellulose nanocrystal reinforced composite material is 30.0% to 80.0%, for example, 35.0%, 40.0%, 45.0%, 50.0%, 55.0%, 60.0%, 65.0%, 70.0% or 75.0%.
[0023] In the present invention, the mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material is preferably 30.0% to 80.0%. If the mass percentage of the composite fiber is too low, the strength of the prepared cellulose nanocrystal reinforced composite material is low; if the mass percentage of the composite fiber is too high, the adhesive cannot completely infiltrate and coat the composite fiber and cannot form effective bonding to the composite fiber.
[0024] Preferably, the diameter of the microchannel extrusion outlet of the microfluidic device in step (1) and step (3) is independently 10.0-300.0 μm, for example, 30.0 μm, 60.0 μm, 90.0 μm, 120.0 μm, 150.0 μm, 180.0 μm, 210.0 μm, 240.0 μm or 270.0 μm, etc.
[0025] In the present invention, the diameter of the microchannel extrusion port of the microfluidic device is 10.0-300.0 μm. Those skilled in the art can select the diameter of the microchannel extrusion port of the microfluidic device required in step (1) and step (3) according to the diameter of the composite fiber to be prepared and the mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material.
[0026] Preferably, the mixing in step (1) is performed by using a twin-screw extruder.
[0027] Preferably, the extrusion rates of step (1) and step (3) are each independently 0.5 to 6.0 m / min, for example, 1.0 m / min, 1.5 m / min, 2.0 m / min, 2.5 m / min, 3.0 m / min, 3.5 m / min, 4.0 m / min, 4.5 m / min, 5.0 m / min or 5.5 m / min, etc.
[0028] Preferably, the mixing in step (2) is performed using a planetary centrifugal mixer.
[0029] It should be noted that the curing temperature and other conditions can be adjusted by those skilled in the art according to the adhesive system used.
[0030] Preferably, the preparation method specifically comprises the following steps:
[0031] (1) Cellulose nanocrystals and a polymer resin are mixed and extruded through a microfluidic device to obtain composite fibers, wherein the diameter of the composite fibers is 10.0 to 200.0 μm.
[0032] (2) Mixing cellulose nanocrystals and an adhesive to obtain a mixed colloid, wherein the mass percentage of the cellulose nanocrystals in the mixed colloid is 5.0% to 30.0%.
[0033] (3) The composite fiber obtained in step (1) is passed through a microfluidic device containing the mixed colloid obtained in step (2) in a microchannel, to be pulled and extruded to obtain fibers with the mixed colloid coated on the surface, and solidified to obtain the cellulose nanocrystal reinforced composite material, wherein the mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material is 30.0% to 80.0%.
[0034] Step (1) and step (2) may be performed in any order or simultaneously.
[0035] In a second aspect, the present invention provides a cellulose nanocrystal reinforced composite material, wherein the cellulose nanocrystal reinforced composite material is prepared by the preparation method described in the first aspect.
[0036] In a third aspect, the present invention provides an application of the cellulose nanocrystal reinforced composite material as described in the second aspect in a mobile phone back shell material or an automobile bumper material.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] In the present invention, the cellulose nanocrystals in the composite fiber are oriented along the extrusion direction, which greatly improves the mechanical properties of the polymer resin matrix, so that the prepared cellulose nanocrystal reinforced composite material has excellent mechanical properties; in the preparation process of the cellulose nanocrystal reinforced composite material, the cellulose nanocrystals in the mixed colloid are oriented along the composite fiber direction, which enhances the bonding strength and plays an effective connecting role between the composite fibers. The cellulose nanocrystals are oriented in the same direction in the composite fiber and the mixed colloid, respectively, forming a dual-oriented structure, and the two have a synergistic effect. The prepared cellulose nanocrystal reinforced composite material has excellent mechanical properties, and the flexural strength of the cellulose nanocrystal reinforced composite material is 64.9~86.1MPa, and the flexural modulus is 3.2~5.9 GPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the process of step (3) of Example 1;
[0040] Among them, 1-composite fiber; 2-mixed colloid; 3-microfluidic device; 4-fluid driving device; 5-pulling roller; 6-substrate for stacking fibers with surfaces coated with mixed colloid; 7-cellulose nanocrystal reinforced composite material. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0042] The sources of some components in the embodiments and comparative examples are as follows:
[0043] Cellulose nanocrystals: brand name CEOLUS FD-101, manufacturer: Asahi Chemicals Corporation;
[0044] Polypropylene: Brand name is NOVATEC MA04A, manufacturer is Japan Polypropylene Co., Ltd.;
[0045] High-density polyethylene: brand 7000F, manufacturer: Prime Polymer Company;
[0046] Polyurethane adhesive: The brand is Macroplast PU 8202, and the manufacturer is Henkel Chemical Materials (Shanghai) Co., Ltd.
[0047] Example 1
[0048] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material, the preparation method comprising the following steps:
[0049] (1) 5.0 parts by weight of cellulose nanocrystals and 95.0 parts by weight of polypropylene are mixed through a twin-screw extruder to form a premix. The premix is heated and melted to obtain a mixed fluid, which is extruded through a microfluidic device at an extrusion rate of 0.5 m / min. The mixed fluid is air-cooled to obtain a composite fiber, wherein the diameter of the composite fiber is 20 μm.
[0050] (2) Cellulose nanocrystals and polyurethane adhesive (Macroplast PU 8202) were mixed by a planetary centrifugal mixer to obtain a uniformly dispersed mixed colloid, wherein the mass percentage of cellulose nanocrystals in the mixed colloid was 30%.
[0051] (3) If Figure 1As shown, the composite fiber obtained in step (1) is passed through a microfluidic device containing the mixed colloid obtained in step (2) in a microchannel, and is pulled by a pulling roller to extrude the fiber with the surface coated with the mixed colloid. The extrusion rate is 6 m / min. The extruded fibers with the surface coated with the mixed colloid are stacked and arranged in parallel. The mixed colloids are in contact with each other to form a sheet. The sheet is cured at 75° C. for 240 min to obtain the cellulose nanocrystal reinforced composite material. The mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material is 30%.
[0052] Example 2
[0053] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material, the preparation method comprising the following steps:
[0054] (1) 5.0 parts by weight of cellulose nanocrystals and 95.0 parts by weight of polypropylene are mixed through a twin-screw extruder to form a premix. The premix is heated and melted to obtain a mixed fluid, which is extruded through a microfluidic device. The diameter of the microchannel extrusion port of the microfluidic spinning device is 20 μm, and the extrusion rate is 6 m / min. Composite fibers are obtained after air cooling. The diameter of the composite fibers is 20 μm.
[0055] (2) Cellulose nanocrystals and polyurethane adhesive (Macroplast PU 8202) were mixed by a planetary centrifugal mixer to obtain a uniformly dispersed mixed colloid, wherein the mass percentage of cellulose nanocrystals in the mixed colloid was 30%.
[0056] (3) The composite fiber obtained in step (1) passes through a microfluidic device containing the mixed colloid obtained in step (2) in a microchannel, is pulled by a pulling roller, and is extruded to obtain fibers with the surface coated with the mixed colloid. The extrusion rate is 6 m / min. The extruded fibers with the surface coated with the mixed colloid are stacked and arranged in parallel. The mixed colloids are in contact with each other to merge into a sheet. The sheet is cured at 75° C. for 240 min to obtain the cellulose nanocrystal reinforced composite material. The mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material is 30%.
[0057] Example 3
[0058] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material, the preparation method comprising the following steps:
[0059] (1) 2.5 parts by weight of cellulose nanocrystals and 97.5 parts by weight of high-density polyethylene are formed into a premix by a twin-screw extruder. The premix is heated and melted to obtain a mixed fluid which is extruded through a microfluidic device. The diameter of the microchannel extrusion port of the microfluidic device is 20 μm. The extrusion rate is 0.5 m / min. Composite fibers are obtained after air cooling. The diameter of the composite fibers is 20 μm.
[0060] (2) Cellulose nanocrystals and polyurethane adhesive (Macroplast PU 8202) were mixed by a planetary centrifugal mixer to obtain a uniformly dispersed mixed colloid, wherein the mass percentage of cellulose nanocrystals in the mixed colloid was 30%.
[0061] (3) The composite fiber obtained in step (1) passes through a microfluidic device containing the mixed colloid obtained in step (2) in a microchannel, is pulled by a pulling roller, and is extruded to obtain fibers with the surface coated with the mixed colloid. The extrusion rate is 6 m / min. The extruded fibers with the surface coated with the mixed colloid are stacked and arranged in parallel. The mixed colloids are in contact with each other to merge into a sheet. The sheet is cured at 75° C. for 240 min to obtain the cellulose nanocrystal reinforced composite material. The mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material is 30%.
[0062] Example 4
[0063] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the weight fraction of the cellulose nanocrystals in step (1) is adjusted to 10 parts, and the weight fraction of polypropylene is adjusted to 90 parts. Other conditions are the same as those in embodiment 1.
[0064] Example 5
[0065] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material in step (3) is adjusted to 80%, and other conditions are the same as those in embodiment 1.
[0066] Example 6
[0067] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of the composite fiber in the cellulose nanocrystal reinforced composite material in step (3) is adjusted to 50%, and other conditions are the same as those in embodiment 1.
[0068] Example 7
[0069] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material, which differs from Embodiment 1 only in that the diameter of the composite fiber in step (1) is adjusted to 200 μm, and other conditions are the same as those in Embodiment 1.
[0070] Example 8
[0071] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material, which differs from Embodiment 1 only in that the diameter of the composite fiber in step (1) is adjusted to 100 μm, and other conditions are the same as those in Embodiment 1.
[0072] Example 9
[0073] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of cellulose nanocrystals in the mixed colloid in step (2) is adjusted to 5%, and other conditions are the same as those in embodiment 1.
[0074] Example 10
[0075] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The difference between this method and embodiment 1 is that the mass percentage of cellulose nanocrystals in the mixed colloid in step (2) is adjusted to 10%, and other conditions are the same as those in embodiment 1.
[0076] Embodiment 11
[0077] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of cellulose nanocrystals in the mixed colloid in step (2) is adjusted to 15%, and other conditions are the same as those in embodiment 1.
[0078] Example 12
[0079] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of cellulose nanocrystals in the mixed colloid in step (2) is adjusted to 20%, and other conditions are the same as those in embodiment 1.
[0080] Example 13
[0081] This embodiment provides a method for preparing a cellulose nanocrystal-reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of cellulose nanocrystals in the mixed colloid in step (2) is 25%, and other conditions are the same as those in embodiment 1.
[0082] Embodiment 14
[0083] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material, which differs from Embodiment 1 only in that the curing temperature of the mixed colloid in step (3) is 100° C. and the curing time is 60 minutes. Other conditions are the same as those in Embodiment 1.
[0084] Embodiment 15
[0085] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of composite fibers in the cellulose nanocrystal reinforced composite material in step (3) is adjusted to 25%, and other conditions are the same as those in embodiment 1.
[0086] Example 16
[0087] This embodiment provides a method for preparing a cellulose nanocrystal reinforced composite material. The only difference between this method and embodiment 1 is that the mass percentage of composite fibers in the cellulose nanocrystal reinforced composite material in step (3) is adjusted to 85%, and other conditions are the same as those in embodiment 1.
[0088] Comparative Example 1
[0089] This comparative example provides a method for preparing a cellulose nanocrystal reinforced composite material, which differs from Example 1 only in that the preparation method does not include step (2), and in step (3), the mixed colloid is replaced with a polyurethane adhesive (Macroplast PU 8202) of the same weight, and other conditions are the same as those in Example 1.
[0090] Comparative Example 2
[0091] This comparative example provides a method for preparing a cellulose nanocrystal-reinforced composite material, which differs from Example 1 only in that the weight fraction of the cellulose nanocrystals in step (1) is adjusted to 1.5 parts, and the weight fraction of polypropylene is adjusted to 98.5 parts, and other conditions are the same as those in Example 1.
[0092] Comparative Example 3
[0093] This comparative example provides a method for preparing a cellulose nanocrystal-reinforced composite material, which differs from Example 1 only in that the weight fraction of the cellulose nanocrystals in step (1) is adjusted to 15 parts, and the weight fraction of polypropylene is adjusted to 85 parts, and other conditions are the same as those in Example 1.
[0094] Comparative Example 4
[0095] This comparative example provides a method for preparing a cellulose nanocrystal-reinforced composite material, which differs from Example 1 only in that cellulose nanocrystals are not added in step (1), the weight portion of polypropylene is 100 parts, and other conditions are the same as those in Example 1.
[0096] The cellulose nanocrystal reinforced composite materials provided in the above examples and comparative examples were subjected to the following tests.
[0097] Bending performance test: Tested according to GB / T 9341-2000 to obtain bending strength and bending modulus.
[0098] The test results are shown in Table 1 below.
[0099] Table 1
[0100]
[0101] It can be seen from the contents of Table 1 that the cellulose nanocrystal reinforced composite material prepared by the preparation method of the cellulose nanocrystal reinforced composite material provided in Examples 1-16 has a flexural strength of 64.9-86.1 MPa and a flexural modulus of 3.2-5.9 GPa.
[0102] Compared with Example 1, Example 7 and Example 8, as the diameter of the composite fiber increases, the bending strength of the prepared cellulose nanocrystal reinforced composite material increases.
[0103] Compared with Example 1 and Examples 9 to 13, as the mass percentage of cellulose nanocrystals in the mixed colloid increases, the flexural strength and flexural modulus first increase and then decrease; when the mass percentage of cellulose nanocrystals in the mixed colloid is 30%, the flexural strength of the prepared cellulose nanocrystal reinforced composite material decreases. This is because when the content of cellulose nanocrystals in the mixed colloid is high, the degree of orientation of the cellulose nanocrystals decreases.
[0104] Compared with Example 1, if the curing temperature in step (3) is increased, the curing time can be reduced accordingly (Example 14), and the properties of the obtained composite material do not change significantly.
[0105] Compared with Example 1, if the mass percentage of composite fibers in the cellulose nanocrystal reinforced composite material is too low (Example 15), the flexural strength of the prepared cellulose nanocrystal reinforced composite material is low; if the mass percentage of composite fibers in the cellulose nanocrystal reinforced composite material is too high (Example 16), the flexural modulus of the prepared cellulose nanocrystal reinforced composite material is reduced. The reason is that the adhesive cannot completely infiltrate and coat the composite fibers and form an effective bond with them. It can be seen that by controlling the mass percentage of composite fibers in the cellulose nanocrystal reinforced composite material within a specific range, the prepared cellulose nanocrystal reinforced composite material has better performance.
[0106] Compared with Example 1, if the preparation method does not include step (2) and the polyurethane adhesive replaces the mixed colloid (Comparative Example 1), the flexural strength and flexural modulus of the prepared cellulose nanocrystal reinforced composite material are both low.
[0107] Compared with Example 1, if the mass percentage of cellulose nanocrystals in the composite fiber is too low (Comparative Example 2), the flexural strength and flexural modulus of the prepared cellulose nanocrystal reinforced composite material are both low; if the mass percentage of cellulose nanocrystals in the composite fiber is too high (Comparative Example 3), the flexural strength and flexural modulus of the prepared cellulose nanocrystal reinforced composite material are sharply reduced. It can be seen that by controlling the mass percentage of cellulose nanocrystals in the composite fiber within a specific range, the prepared cellulose nanocrystal reinforced composite material has better performance.
[0108] Compared with Example 1, if cellulose nanocrystals are not added in step (1) (Comparative Example 4), the fiber flexural strength and modulus of the single polymer polypropylene are low, and the flexural strength and flexural modulus of the prepared cellulose nanocrystal reinforced composite material are low.
[0109] The applicant declares that the present invention illustrates a cellulose nanocrystal reinforced composite material and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a cellulose nanocrystal reinforced composite material, characterized in that: The preparation method comprises the following steps: (1) mixing cellulose nanocrystals and a polymer resin, and extruding the mixture through a microfluidic device to obtain composite fibers, wherein the mass percentage of the cellulose nanocrystals in the composite fibers is 2.5% to 10.0%; (2) mixing cellulose nanocrystals and an adhesive to obtain a mixed colloid; (3) passing the composite fiber obtained in step (1) through a microfluidic device containing the mixed colloid obtained in step (2) in a microchannel, pulling and extruding to obtain fibers with the mixed colloid coated on the surface, and curing to obtain the cellulose nanocrystal reinforced composite material; The diameters of the microchannel extrusion outlets of the microfluidic devices in step (1) and step (3) are independently 10.0 to 300.0 μm; The extrusion rates of step (1) and step (3) are each independently 0.5 to 6.0 m / min; The mass percentage of cellulose nanocrystals in the mixed colloid in step (2) is 5.0% to 30.0%; The polymer resin includes any one or a combination of at least two of polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyamide, polycarbonate or acrylonitrile-butadiene-styrene copolymer; The adhesive includes any one of epoxy resin adhesive, acrylate adhesive, polyurethane adhesive or silicone adhesive, or a combination of at least two of them.
2. The preparation method according to claim 1, characterized in that: The diameter of the composite fiber is 10.0-200.0 μm.
3. The preparation method according to claim 1, characterized in that: The polyurethane adhesive includes two-component polyurethane and / or one-component polyurethane.
4. The preparation method according to claim 1, characterized in that: The polyurethane adhesive comprises water-based polyurethane.
5. The preparation method according to claim 1, characterized in that: The polyurethane adhesive includes ultraviolet light curing polyurethane.
6. The preparation method according to claim 1, characterized in that: The mass percentage of composite fibers in the cellulose nanocrystal reinforced composite material is 30.0% to 80.0%; The mixing in step (1) is performed by using a twin-screw extruder; The mixing in step (2) is performed using a planetary centrifugal mixer.
7. A cellulose nanocrystal reinforced composite material, characterized in that: The cellulose nanocrystal reinforced composite material is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the cellulose nanocrystal reinforced composite material as claimed in claim 7 in a mobile phone back shell material or an automobile bumper material.
Citation Information
Patent Citations
Preparation method of composite material with fiber surface coated with cellulose nano crystals and used for multi-scale enhancement
CN105131529A
Method for preparing high-adhesion water-borne adhesive based on polymer compound
CN105462523A